Optimization of Data Processing Structure for Multi-Position Radar Surveillance Systems - Obod, I.; Svyd, I.; Vorgul, O.; Maltsev, O.; Datsenko, O.; Boiko, N. (UKRCON, 2021)
The optimal structure for processing signal data and primary processing data of a multi-position radar system is synthesized in this paper. In this work, due to the creation of an information base for storing signal data on the required number of scans of a multi-position radar system, it is possible to merge data both at the level of signal data and at the level of primary data processing. Each element of the last stores both signal data and indicators of the quality of their receipt. This made it possible to carry out inter-stage optimization of signal data processing and primary data processing.
Keywords: multi-position radar system; air object; data processing